Heating, Ventilating, and Air Conditioning Analysis and Design - McQuiston, Faye C.; Parker, Jerald D.; Spitler, Jeffrey D.; Taherian, Hessam (John Wiley & Sons, 2024)
Now in its Seventh Edition, Heating, Ventilating, and Air Conditioning has been fully updated to align with the latest technologies and industry developments while maintaining the balance of theoretical information with practical applications that has prepared many generations of students for their careers. As they work through the book, students will become familiar with different types of heating and air conditioning systems and equipment, understand processes and concepts involving moist atmospheric air, learn how to provide comfort to occupants in controlled spaces, and gain practice calculating probable heat loss/gain and energy requirements. A companion website includes additional multiple-choice questions, tutorial videos showing problem-solving for R-value calculation, and Excel spreadsheets that can be used for practice calculations. The Seventh Edition includes new coverage of ductless A/C systems, heat exchangers and hybrid heat pumps, geothermal heat pumps, energy-efficient equipment, and UV principles of air quality treatment of airborne viruses like COVID-19.